Miles To Go : The Second Journal of The Walk - Evans, Richard Paul (Thorndike, Me. : Center Point Large Print, 2011)
A successful executive finds he has lost his wife, his home, and his business quite suddenly. He starts walking cross-country to Key West, but he is stabbed and confined to a hospital for a long, difficult recovery. A mysterious woman invites him into her home, and he soon finds that to complete his journey, he must help her with her own.
Keywords: Executives -- Fiction; Life change events -- Fiction; Walking -- Fiction -- United States; Voyages and travels -- Fiction; Identity (Psychology) -- Fiction; Loss (Psychology) -- Fiction; Diaries -- Fiction; Large type books